DEVICE FOR CHANGE OF TONGUE LOCATION AND TENSION OF ITS BRIDLE - Golovko, N.V.; Ганнам Іяд Наджиб (World of Medicine and Biology, 2012)
In article the substantiation of application of the device for myogymnastic exercise is presented at shortening of a bridle of language, the schematic image of a design, the indication to application and myogymnastic exercise is given.